Expression of ALS‐linked TDP‐43 mutant in astrocytes causes non‐cell‐autonomous motor neuron death in rats. (28th May 2013) - Tong, Jianbin; Huang, Cao; Bi, Fangfang; Wu, Qinxue; Huang, Bo; Liu, Xionghao; Li, Fang; Zhou, Hongxia; Xia, Xu‐Gang
<x xml:space="preserve">Abstract</x> Mutation of Tar DNA‐binding protein 43 (TDP‐43) is linked to amyotrophic lateral sclerosis. Although astrocytes have important roles in neuron function and survival, their potential contribution to TDP‐43 pathogenesis is unclear. Here, we created novel lines of transgenic rats that express a mutant form of human TDP‐43 (M337V substitution) restricted to astrocytes. Selective expression of mutant TDP‐43 in astrocytes caused a progressive loss of motor neurons and the denervation atrophy of skeletal muscles, resulting in progressive paralysis. The spinal cord of transgenic rats also exhibited a progressive depletion of the astroglial glutamate transporters GLT‐1 and GLAST. Astrocytic expression of mutant TDP‐43 led to activation of astrocytes and microglia, with an induction of the neurotoxic factor Lcn2 in reactive astrocytes that was independent of TDP‐43 expression. These results indicate that mutant TDP‐43 in astrocytes is sufficient to cause non‐cell‐autonomous death of motor neurons. This motor neuron death likely involves deficiency in neuroprotective genes and induction of neurotoxic genes in astrocytes.